2019
DOI: 10.3390/ijerph16071199
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation Characteristics of Ecosystem Service Losses in the Agro-Pastoral Ecotone of Northern China

Abstract: Being subject to climate change and human intervention, the land-use pattern in the agro-pastoral ecotone of Northern China has undergone complex changes over the past few decades, which may jeopardize the provision of ecosystem services. Thus, for sustainable land management, ecosystem services should be evaluated and monitored. In this study, based on Landsat TM/ETM data, we quantitatively evaluated the losses of ecosystem service values (ESV) in three sections of the agro-pastoral ecotone from 1980–2015. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…In China, the APEs area spans throughout the whole mainland from northeast to southwest, covering 13.35% of China's land area (1.29 million km 2 ), with residential populations and grain yield accounting for 4.68% (59.30 million) and 7.98% of the total population and grain yield of China, respectively [3]. Therefore, the arid and semiarid agropastoral ecotone of northern China (hereafter APENC) is a typical ecologically transitional zone (largest in area and the longest in spatial scale), which effectively prevents the desert in the northwest from spreading south and east [4]. Therefore, the APENC is a crucial ecological barrier for ecological security and a primary area for social and economic development in China.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the APEs area spans throughout the whole mainland from northeast to southwest, covering 13.35% of China's land area (1.29 million km 2 ), with residential populations and grain yield accounting for 4.68% (59.30 million) and 7.98% of the total population and grain yield of China, respectively [3]. Therefore, the arid and semiarid agropastoral ecotone of northern China (hereafter APENC) is a typical ecologically transitional zone (largest in area and the longest in spatial scale), which effectively prevents the desert in the northwest from spreading south and east [4]. Therefore, the APENC is a crucial ecological barrier for ecological security and a primary area for social and economic development in China.…”
Section: Introductionmentioning
confidence: 99%
“…The Institute of Geographic Sciences and Natural Resources Research provided the gross domestic production (GDP) and population data of 1-km grids. In these datasets, many factors closely related to GDP and population, such as land use type, light intensity values at night, and densities of residential areas, were comprehensively considered [10,31].…”
Section: Data Sourcesmentioning
confidence: 99%
“…2021, 5, 54 2 of 16 economic and social development [9]. The Millennium Ecosystem Assessment reported that 15 of 24 ecosystem services worldwide showed a tendency toward degradation in the last half century [10,11]. Owing to human interference, the provision of ecosystem services decreased by 60% over this time period [12].…”
Section: Introductionmentioning
confidence: 99%
“…The ESV is an estimate of ecosystem services and natural capital using economic laws. Costanza's approach to estimating ESV is widely used [32,48]. As land use pattern is the most important factor in the supply of ecosystem services, we utilized the Landsat 5 TM and Landsat 8 OLI remote sensing data to assess changes in ESV over temporal and spatial scales.…”
Section: Construction Of Ecological Landscape Key Area Recognition Inmentioning
confidence: 99%
“…The biomass-based ESV adjustment method is shown in formula (4), with a correction factor of 0.44 for determining grassland biomass in Inner Mongolia [49]. Nine indicators of ESV were selected and divided into four categories [48]: supply service (food supply, raw supply); regulation service (atmospheric regulation, climate regulation, hydrological regulation, waste disposal, and soil conservation); support service (biodiversity); and cultural service (landscape aesthetics) [50].…”
Section: Construction Of Ecological Landscape Key Area Recognition Inmentioning
confidence: 99%